1974
DOI: 10.1042/bj1430745
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the soluble adenosine triphosphatase from mitochondria by adenylyl imidodiphosphate

Abstract: 1. Adenylyl imidodiphosphate is an inhibitor with high affinity for the soluble ATPase (adenosine triphosphatase) from mitochondria. 2. The reaction of the inhibitor with the ATPase is slow and estimates for the association and dissociation reaction rate constants are given. 3. The number of binding sites for the inhibitor appears to be doubled in the presence of 2,4-dinitrophenol. 4. Adenylyl imidodiphosphate is less effective as an inhibitor of the ATPase activity of this enzyme than of the inosine triphosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1975
1975
1993
1993

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…1, the inhibition is substantial (compare with trace a) but not as great as the maximal inhibition produced when zinc is present initially (trace c). Trace d also shows that inhibition by zinc is time dependent but fairly rapid on the time scale of these experiments with a f,, of about 2 s (estimated by fitting a first-order exponential expression to the development of inhibition [22] by non-linear regression). This time dependence may lead to an underestimation of inhibition, particularly at low zinc concentrations.…”
Section: Resultsmentioning
confidence: 80%
“…1, the inhibition is substantial (compare with trace a) but not as great as the maximal inhibition produced when zinc is present initially (trace c). Trace d also shows that inhibition by zinc is time dependent but fairly rapid on the time scale of these experiments with a f,, of about 2 s (estimated by fitting a first-order exponential expression to the development of inhibition [22] by non-linear regression). This time dependence may lead to an underestimation of inhibition, particularly at low zinc concentrations.…”
Section: Resultsmentioning
confidence: 80%
“…2). Philo & Selwyn (1974) and Schuster et al (1975Schuster et al ( , 1976 believe that the hydrolysis of ATP and GTP occurs in the different nucleotide-binding sites of factor F1. However, the results obtained by us (the inhibition of the ATPase and GTPase activities of factor F1 as the result of binding by the enzyme of one nucleotide residue) are in better agreement with the suggestion that the hydrolysis of ATP and GTP occurs in one and the same site of factor F1.…”
Section: Resultsmentioning
confidence: 99%
“…At pH 7.8, k+4 is 6.7 x 10-2 S-1, k4 is 3.8 x 10-3S-1 and K q is 17.6. Therefore k+4 is higher than k 4, indicating that EI* will be favoured over EI and thus explaining the stability of the inhibition of the ATPase (Philo & Selwyn, 1974;Harris et al, 1978).…”
Section: Kinetic Parametermentioning
confidence: 99%
“…[fly-Imido]ATP has also been shown to be a potent competitive inhibitor of F1-ATPase activity (Schuster et al, 1975a), of the ATP-dependent reduction of NAD+ by succinate and of ATP-[32P]P1 exchange; however, it does not affect the ATP synthesis from ADP and Pi (Penefsky, 1974). [f7-Imido]ATP inhibits F1-0306-3283/83/030727-09$2.00 (© 1983 The Biochemical Society ATPase in a time-dependent manner, forming a relatively stable complex (Philo & Selwyn, 1974;Harris et al, 1978), and Harris et al (1981) have shown that it inhibits by binding to the hydrolytic site of the enzyme. The stoicheiometry of the binding has been studied, and the presence of three exchangeable binding sites that are distinct from non-catalytic sites, i.e.…”
mentioning
confidence: 99%